Migraine management - Marfil Rivera, Alejandro (UANL. Facultad de Medicina, 2015)
Migraines are common illnesses. Studies conducted in 12 Latin American cities, including two in Mexico, have found that its prevalence in our country is 15%. The rate in gender is 3:1 (Women/Men) worldwide. The diagnostic criteria for migraines were published for the first time in 1988, in the first edition of the International Headache Classification, promoted by the International Headache Society, with its second edition in 2003, and a third beta version that will probably be published in 2015. Diagnostic criteria for the different forms of migraines were first described in this document, which has simplified communication among doctors and made possible comparisons between studies. The current migraine criteria (with and without aura) are shown in Table 1. As in all primary headaches, paraclinic and imaging studies are normal and rarely necessary, exception made for the cases where there is clinical doubt or whenever the patient is too anxious and wishes to be ‘‘as certain as you can be’’. This may be a valid reason; however it may increase the cost of medical attention and can be problematic in institutions with a high volume of patients.